2004
DOI: 10.1136/bjo.2003.028480
|View full text |Cite
|
Sign up to set email alerts
|

Twelve hour reproducibility of choroidal blood flow parameters in healthy subjects

Abstract: Aims/background: To investigate the reproducibility and potential diurnal variation of choroidal blood flow parameters in healthy subjects over a period of 12 hours. Methods: The choroidal blood flow parameters of 16 healthy non-smoking subjects were measured at five time points during the day (8:00, 11:00, 14:00, 17:00, and 20:00). Outcome parameters were pulsatile ocular blood flow as assessed by pneumotonometry, fundus pulsation amplitude as assessed by laser interferometry, blood velocities in the opthalmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 29 publications
(14 reference statements)
3
53
2
Order By: Relevance
“…Experience of the investigators and internal quality control is important because it is known that CDI in general is a subjective measurement. 17 In our laboratory, we reach acceptable reproducibility of the CDI measurements by maximal standardization of the CDI procedure. 18 Compared to previous reports, the diameter of the OA as well as that of the CRA appears to be slightly overestimated.…”
Section: Discussionmentioning
confidence: 73%
“…Experience of the investigators and internal quality control is important because it is known that CDI in general is a subjective measurement. 17 In our laboratory, we reach acceptable reproducibility of the CDI measurements by maximal standardization of the CDI procedure. 18 Compared to previous reports, the diameter of the OA as well as that of the CRA appears to be slightly overestimated.…”
Section: Discussionmentioning
confidence: 73%
“…[9][10][11][12][13] Previous studies showed that variations in ocular blood flow throughout the diurnal/ wake period were not significant in both younger and older adults. 20,31 One study suggested that ocular blood flow in the optic nerve head decreased at the end of the diurnal/wake period in younger adults. 32 In the present study, we extended the measurement times into the nocturnal/sleep period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a precise clinical evaluation of choroidal morphology should be important for understanding the pathogenesis of many retinal and choroidal diseases. 16,17 To date, SD-OCT featuring high resolution and scanning speeds has allowed the choroid to be assessed in vivo. 12 N2: choroidal thickness at 1000 μm nasal to the fovea; N1: choroidal thickness at 500 μm nasal to the fovea; F: choroidal thickness at fovea; T1: choroidal thickness at 500 μm temporal to the fovea; T2: choroidal thickness at 1000 μm temporal to the fovea; T3: choroidal thickness at 1500 μm temporal to the fovea.…”
Section: Discussionmentioning
confidence: 99%